2004
DOI: 10.1002/pmic.200300723
|View full text |Cite
|
Sign up to set email alerts
|

Differential protein composition of bovine whey: A comparison of whey from healthy animals and from those with clinical mastitis

Abstract: During clinical mastitis in dairy cows, the quantity of milk produced decreases and the composition of the milk is altered. As the severity of inflammation associated with the disease increases, the chemical composition of milk approaches that of blood as a consequence of increased permeability of the blood mammary barrier, or de novo intramammary synthesis, as has been suggested for mammary associated serum amyloid A3. A better understanding of these events may provide new approaches for the diagnosis and tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
139
3
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(159 citation statements)
references
References 20 publications
13
139
3
4
Order By: Relevance
“…This is in part due to the dominance of the six major milk proteins (a S1 -casein, a S2 -casein, b-casein, k-casein, b-lactoglobulin and a-lactalbumin), and the unavailability, until recently, of suitable high-resolution protein separation methods, and sensitive identification technologies. Initial studies resolving milk proteins by two-dimensional electrophoresis and identifying them using MS identified only a small number of additional proteins (Hogarth et al, 2004). However, with the continued development of proteomics technologies and improvement of bovine protein sequence databases, a hitherto hidden complexity has been revealed in the repertoire of proteins present in milk.…”
Section: Proteomicsmentioning
confidence: 99%
“…This is in part due to the dominance of the six major milk proteins (a S1 -casein, a S2 -casein, b-casein, k-casein, b-lactoglobulin and a-lactalbumin), and the unavailability, until recently, of suitable high-resolution protein separation methods, and sensitive identification technologies. Initial studies resolving milk proteins by two-dimensional electrophoresis and identifying them using MS identified only a small number of additional proteins (Hogarth et al, 2004). However, with the continued development of proteomics technologies and improvement of bovine protein sequence databases, a hitherto hidden complexity has been revealed in the repertoire of proteins present in milk.…”
Section: Proteomicsmentioning
confidence: 99%
“…Albumin is a plasma protein whose elevation in milk indicates disintegration of the blood-milk barrier (Vangroenweghe et al, 2004). The observed elevation in milk albumin after high-dose post-ruminal infusion of LNA was consistent with changes in the protein composition of milk seen during naturally and experimentally induced mastitis (Hogarth et al, 2004;Boehmer et al, 2008;Boehmer et al, 2010;Ibeagha-Awemu et al, 2010). In the current study, the elevated albumin and SCC in milk were accompanied by disintegration of the blood-milk barrier, suggesting a metabolic stress of mammary gland owing to the LNA infusion.…”
Section: Discussionmentioning
confidence: 55%
“…The use of comparative proteomics to analyse differential milk protein expression in whey from milk collected from healthy cows and cows with subclinical mastitis, is highly significant for its effectiveness in finding biological marker molecules and elucidating the pathological mechanisms of the disease. Research has taken place into protein expression patterns in whey from milk from healthy cows and cows with clinical mastitis, and it was found that some identified proteins were associated with the mastitis (14,18). These results indicated that protein expression patterns changed in whey from subclinical mastitis cases, and that proteomic methods could be used to find new diagnostic markers of the disease.…”
Section: Introductionmentioning
confidence: 99%